A switch capacitor KVAr and selective harmonic current compensator - Marouchos, Christos; Darwich, Μ.; Evdokimou, M. (My University, 2014)
The high penetration of renewable electrical energy sources into the power grid is highlighting the problem of harmonics. Eliminating line current harmonics is taken very seriously in HVDC transmission where the ac/dc/ac conversion process is the source of mains pollution. The need for high efficiency and low harmonic content for grid-connected inverters is high. The oldest topology still used in hvdc is the line-commutated 3-level thyristor inverter, characterised by low losses due to the inherent low switching rate. The high content of harmonics and the bulky passive filters to minimize them, makes this solution non-attractive and has let the way to new topologies and modes of operation of inverters. In this paper though it is suggested to keep the 3-level thyristor grid connected inverter for its robustness and high efficiency and replace the bulky passive filters with switched capacitor filters. A new active filter, the DSSC circuit is investigated here and its ability to cancel a band of lower harmonics is reported.
Keywords: Active filters; Switched capacitors; Harmonic current elimination